Cross-Cultural Bayesian Network Analysis of Factors Affecting Residents’ Concerns About the Spread of an Infectious Disease Caused by Tourism - Glückstad, Fumiko Kano; Wiil, Uffe Kock; Mansourvar, Marjan; Andersen, Pernille Tanggaard (Frontiers in Psychology, 2021)
COVID-19 has had a severe impact globally and the recovery can be characterized as a tug of war between fast economic recovery and firm control of further virus-spread. To be prepared for future pandemics, public health policy makers should put effort into fully understanding any complex psychological tensions that inherently arise between opposing human factors such as free enjoyment versus self-restriction. As the COVID-19 crisis is an unusual and complex problem, combinations of diverse factors such as health risk perception, knowledge, norms & beliefs, attitudes and behaviors are closely associated with individuals’ intention to enjoy the experience economy but also their concerns that the experience economy will trigger further spread of the infectious diseases. Our aim is to try identifying what factors are associated with their concerns about the spread of the infectious disease caused by the local experience economy. Hence, we have chosen the “data-driven” explanatory approach, “Probabilistic Structural Equational Modeling”, based on the principle of Bayesian networks to analyze data collected from the following four countries with indicated sample sizes: Denmark (1005), Italy (1005), China (1013) and Japan (1091). Our findings highlight the importance of understanding the contextual differences in relations between the target variable and factors such as personal value priority and knowledge. These factors affect the target variable differently depending on the local severity-level of the infections. Relations between pleasure-seeking via the experience economy and individuals’ anxiety-level about an infectious hotspot seem to differ between East Asians and Europeans who are known to prioritize so-called interpersonal- and independent self-schemes, respectively. Our study also indicates the heterogeneity in the populations, i.e. these relations differ within the respective populations. Another finding shows that the Japanese population is particularly concerned about their local community potentially becoming an infectious hotspot and hence expecting others to comply with their particular social norms. Summarizing, the obtained insights imply the importance of considering both cultural- and individual contexts when policy makers are going to develop measures to address pandemic dilemmas such as maintaining public health awareness and accelerating the recovery of the local experience economy.